Inuit Perspectives on the Significances of Arctic Char (Salvelinus alpinus; Iqaluppik) in Food Security, Health, and Well-being in Nunavik, their Dietary Preferences, and Factors Impacting Fish Quality. - Sara Bolduc; Mélanie Lemire; Jean-Sébastien Moore; Lauréanne Dussault-Desrochers; Kathy Aputiarjuk Snowball; Nancy Etok; Kangirsuk Anguvigaq of; Véronique Nadeau; Matthew Little; Tiff-Annie Kenny; Marianne Falardeau (Arctic Science, 2025)
Arctic Char (Salvelinus alpinus) is a salmonid that is the second-most frequently consumed country food by Inuit in Nunavik, Northern Québec, Canada, valued for its taste, high nutritional quality and low contaminant levels. However, climate change is increasingly impacting Arctic Char, in a region where food insecurity is highly prevalent. Inuit views on this fish are poorly documented yet provide valuable insights for improving food security and health in a context of changing subsistence fisheries. Guided by a community-based participatory research approach, we conducted interviews, focus groups, and workshops in 2022-2023 with Nunavummiut (Inuit of Nunavik) in Kangiqsualujjuaq, Aupaluk, and Kangirsuk. The objectives were to explore (1) the significance of Arctic Char to Inuit diet, culture, health, and well-being, (2) Inuit preferences regarding body parts, preparation methods, and quality attributes, and (3) Inuit knowledge on factors impacting its quality. Participants shared common views on the significance of Arctic Char. Environmental conditions, fish behavior, and fishing methods were linked to the quality of Arctic Char and Inuit-related dietary preferences. Gender roles and generational shifts were highlighted throughout discussions. Inuit shared resilient strategies when facing less preferred fish characteristics, which could help addressing the expected challenges related to climate change.